IMPROVE CAPABILITY PROCESS TO OPTIMIZING PRODUCTIVITY: CASE STUDY LINE PROCESS PACKING ASSEMBLY IN ELECTRONIC MANUFACTURING COMPANY - Mohammad Rofiudin; Dana Santoso Saroso (Operations Excellence: Journal of Applied Industrial Engineering, 2018)
Six sigma is a method for improving processes that focus on reducing process variations using statistical approaches and effective problem solving. The purpose of this method is calculating the impact of six sigma applications to company productivity. Six sigma not only aims to achieve zero defect, with the Six Sigma method optimizing production (Productivity), Six sigma, supporting the proper procedures in line with business goals both system and process. With the DMAIC method, we get as much information as possible and as soon with the smallest sample unit of the experiment. From the results of the paper, Takt Time reduce, 9.2s à  8.5s proved by DMAIC analysis to get effective and efficient improvement that ultimately can improve the company's efficiency.